Laboratory Optimization of Poultry Feather Hydrolysate Application for Soil Fertility: Effects of Soil Texture and Hydrolysate State and Addition Rate - Aditi Roy; Veronika Jílková (Agronomy)
The application of soil organic amendments is a well-established approach to enhancing soil fertility; yet the effects of poultry feather hydrolysate (PFH) on temperate coarse-textured agricultural soils remain underexplored. A six-month microcosm experiment was conducted to determine the effects of PFH in different states (liquid or solid) and addition rates (none, low, or high; i.e., 0, 4, or 8 t dw ha−1, respectively) on microbial activity, nutrient availability and retention, and organic matter (OM) stabilization in two coarse-textured soils (loamy sand or sandy loam). Sandy loam soil exhibited a stronger response to PFH application, supporting 20% higher microbial activity, 35% higher nutrient retention, and 89% higher OM content in soil aggregates compared to loamy sand soil, reflecting enhanced OM stabilization. Moreover, PFH in the liquid state demonstrated more prolonged microbial activity and more sustained release of nutrients compared to the solid state. Finally, at the end of incubation, the high addition rate of PFH significantly increased soil nutrient content by 106%, while the low addition rate limited the increase to 39%, both compared to the no addition rate. Overall, the results suggest that PFH, particularly in the liquid state and at the high addition rate, serves as an effective soil organic amendment, enhancing microbial activity and soil fertility while emphasizing the importance of soil texture in optimizing its application.